Cultivo agroecológico de Tomate Cereja em ambiente protegido no Estado de Roraima - Prado, Rafael Jorge do (2014)
The organic and agroecological farming aims at establishing and maintaining an ecologically balanced and stable agricultural systems, with economic efficiency, good production and be efficient in the use of natural resources. In general, the agroecology uses organic manure as a nutrient source for crops, employing the use of biofertilizers This research included two experiments was conducted in the Universidade Federal de Roraima (UFRR) with cherry tomato (Solanum lycopersicum var. cerasiforme) BRS Iracema and two different types of biofertilizer(ordinary and enriched) applied to the soil of the crop which buckets capacity 12dm3 had previously sieved and limestoned. The drip irrigation was in accordance with the evaporation of class pan A and the need for crop. The first experiment aimed to evaluate the effect of different doses of ordinarybiofertilizers (only bovine biofertilizers) on vegetative and reproductive development of cherry tomato BRS Iracema. The experimental design was a randomized block designwith use of biofertilizers diluted in five ratios (0, 686, 960, 1600 and 2400 mL) with four repetitions. For vegetative variables, it was observed that increasing doses of ordinarybiofertilizer resulted in higher values of the dry mass of leaves, as well as fresh and dry weight of stems. Doses biofertilizer significantly influenced the dry mass of leaves, fresh and dry mass of stems, with possible adjustments quadratic with maximum values between 1275 and 2050 mL/plant. However, the treatments influenced linearly the number of fruits and production. The second experiment aimed to evaluate the effect of different doses of enriched biofertilizer on vegetative and reproductive development of cherry tomato BRS Iracema. The experimental design was a randomized block design with use of enriched biofertilizers diluted in five ratios (0 , 686, 960 , 1600 and 2400 mL/plant with fourrepetitions.The dose of enriched biofertilizer provided an increase in the values of fresh and dry weight of leaves and stems, allowing quadratic adjustments. While the biofertilizer influenced linearly the root dry weight. The enrichedbiofertilizer (2208 ml/plant)provided greater number of fruits (685 fruits per plant), but the doses had no effect on yield.